Strategi Komunikasi Visual Dalam Animasi Iklan Sasa Tepung Bumbu - Hasbullah, Hasbullah; Sumadewa, I Nyoman Yoga; Satria, Christofer (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2024)
Effective visual communication in advertising plays a key role in attracting audience attention and shaping brand image. A well-known kitchen spice brand in Indonesia, advertising animation is used as the main tool to convey the brand message creatively and attractively. However, how effective is animation in increasing brand appeal and strengthening emotional connections with the audience. This research aims to analyze the visual communication strategies implemented in Sasa advertising animations and evaluate their impact on consumer perceptions. Through a qualitative approach and descriptive analysis, this research is based on visual aesthetic theory. The results of this research show that Sasa advertising animations use effective visual communication strategies to convey product messages in an interesting and memorable way. Playful and creative visual elements in animation help simplify information, create positive associations with the brand, and increase consumer engagement. This research provides valuable insight into how visual communication can be optimally utilized in advertising to achieve marketing objectives and strengthen a brand's position in the market.